Encrypt Data with Electromagnetic Waves Using Printable Structures and Materials - Le, Cong Cuong; Dao, Trung Kien; Nguyen, Thanh Huong; Pham, Thi Ngoc Yen (Old Journal, 2020)
In this paper, the authors have analyzed the problem of data encryption by electromagnetic waves, the approach and the challenges that need to be solved, studied the selection of suitable materials to give a new structure design to address printable structure. It will help reducing costs, as well as simplifying production in large quantities. The structure uses a polyimide substrate and conductive ink with a fabrication method of common inkjet technology. The structure is designed based on dipole antenna array for each frequency set. Data is encoded on the basis of determining the feedback power at predetermined frequencies in the range of 3GHz to 9GHz via RCS factor. CST Microwave Studio software is used to design and simulate structures with the ability to encode 5 data bits per frequency set. Encryption structure has a simple design, allowing to improve the data encryption with a small size.